Usulan Peningkatan Efisiensi Keseimbangan Lini Dengan Value Stream Mapping Dan Yamazumi Chart Pada PT.PAI - Sriwana, Iphov K.; Kurniawan, Kurniawan (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2019)
PT. PAI is a footware company that produces sports shoes. The production process at PT. PAI, has a waste of 15.891%. To overcome the problems that occur, this study was conducted with the aim of identifying and proposing waste elimination. The method used is a lean manufacturing approach. One of the tools used is Value Stream Mapping (VSM) and Yamazumi Chart. The first stage to solve the problem is the identification of waste using the Waste Relationship Matrix (WRM), Waste Assessment Questionnaire (WAQ) and VALSAT. The second stage is carried out by designing the current Value Stream Mapping (VSM), designing the proposed improvements using the Yamazumi Chart to balance the production line and designing the Future VSM based on the results of the proposals that have been given. The result of identification using these tools is known that the biggest waste is waste in the process with a percentage of 15.891% followed by overproduction of 15.774%. Based on the calculation using VSM and Yamazumi Chart, elimination of waste can be done as much as 5.48%, reducing the number of workers by 32 people and reducing the number of work stations by 16 work stations